The Influence Of Capital Structure, Company Size, Dividend Policy, And Profitability On Company Value With Covid-19 As A Moderation - Rahmadyaningrum, Ulfa; Masdjojo, Gregorius N (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This research aims to test and analyze the influence of Capital Structure (DER), Company Size (SIZE), Dividend Policy (DPR), and Profitability (ROA) on Company Value (PBV) with Covid-19 as moderation. The sampling method uses a purposive sampling technique with the basic requirement that only mining companies publish complete financial reports and annual reports for the 2017-2022 period. The type of data used is panel data. Selecting the best model in the Chow test to choose between the Common Effect Model (CEM) and the Fixed Effect Model (FEM) and the Hausman test to choose between the Fixed Effect Model (FEM) and the Random Effect Model (REM). Chow and Hausman test results, FEM is the best model in this research. The results of the Fixed Effect Model (FEM) output conclude that Capital Structure has a positive and significant effect on Company Value, Company Size has a negative and significant effect on Company Value, Dividend Policy has a positive and insignificant effect on Company Value, Profitability has a positive and significant effect on Company Value, and Covid-19 (DUMMY) weakens Profitability on Company Value.